Comprehensive structure-activity-relationship of azaindoles as highly potent FLT3 inhibitors. Issue 5 (1st March 2019) - Grimm, Sebastian H.; Gagestein, Berend; Keijzer, Jordi F.; Liu, Nora; Wijdeven, Ruud H.; Lenselink, Eelke B.; Tuin, Adriaan W.; van den Nieuwendijk, Adrianus M.C.H.; van Westen, Gerard J.P.; van Boeckel, Constant A.A.; Overkleeft, Herman S.; Neefjes, Jacques; et al.
Graphical abstract: Abstract: Acute myeloid leukemia (AML) is characterized by fast progression and low survival rates, in which Fms-like tyrosine kinase 3 (FLT3) receptor mutations have been identified as a driver mutation in cancer progression in a subgroup of AML patients. Clinical trials have shown emergence of drug resistant mutants, emphasizing the ongoing need for new chemical matter to enable the treatment of this disease. Here, we present the discovery and topological structure-activity relationship (SAR) study of analogs of isoquinolinesulfonamide H-89, a well-known PKA inhibitor, as FLT3 inhibitors. Surprisingly, we found that the SAR was not consistent with the observed binding mode of H-89 in PKA. Matched molecular pair analysis resulted in the identification of highly active sub-nanomolar azaindoles as novel FLT3-inhibitors. Structure based modelling using the FLT3 crystal structure suggested an alternative, flipped binding orientation of the new inhibitors.